Competing source and loss mechanisms due to wave‐particle interactions in Earth's outer radiation belt during the 30 September to 3 October 2012 geomagnetic storm. Issue 3 (26th March 2014) - Turner, D. L.; Angelopoulos, V.; Li, W.; Bortnik, J.; Ni, B.; Ma, Q.; Thorne, R. M.; Morley, S. K.; Henderson, M. G.; Reeves, G. D.; Usanova, M.; Mann, I. R.; et al.
Abstract Drastic variations of Earth's outer radiation belt electrons ultimately result from various competing source, loss, and transport processes, to which wave‐particle interactions are critically important. Using 15 spacecraft including NASA's Van Allen Probes, THEMIS, and SAMPEX missions and NOAA's GOES and POES constellations, we investigated the evolution of the outer belt during the strong geomagnetic storm of 30 September to 3 October 2012. This storm's main phase dropout exhibited enhanced losses to the atmosphere at L* < 4, where the phase space density (PSD) of multi‐MeV electrons dropped by over an order of magnitude in <4 h. Based on POES observations of precipitating >1 MeV electrons and energetic protons, SAMPEX >1 MeV electrons, and ground observations of band‐limited Pc1‐2 wave activity, we show that this sudden loss was consistent with pitch angle scattering by electromagnetic ion cyclotron waves in the dusk magnetic local time sector at 3 < L* < 4. At 4 < L* < 5, local acceleration was also active during the main and early recovery phases, when growing peaks in electron PSD were observed by both Van Allen Probes and THEMIS. This acceleration corresponded to the period when IMF Bz was southward, the AE index was >300 nT, and energetic electron injections and whistler‐mode chorus waves were observed throughout the inner magnetosphere for >12 h. After this period, Bz turned northward, and injections, chorus activity, and enhancements in PSD ceased. Overall, the outer belt was depleted by this storm. From the unprecedented level of observations available, we show direct evidence of the competitive nature of different wave‐particle interactions controlling relativistic electron fluxes in the outer radiation belt.